The Early Bronze Age settlement of Fidvár, Vráble (Slovakia): reconstructing prehistoric settlement patterns using portable XRF - Gauß, Roland; Bátora, J.; Nowaczinski, Erich; Rassmann, Knut; Schukraft, Gerd (Journal of archaeological science, 2013)
This paper presents first results of chemical analyses of sediment samples from the Early Bronze Age (EBA) settlement Fidvár near Vráble (Slovakia). Large-scale geomagnetic prospection revealed detailed architectural remains of a fortified settlement. Other structures such as an earthwork of the linear pottery culture and at least two Roman march camps were found too. An Auger programme provided sediment samples of different depths, A) from an EBA house and the outer fortification ditch, B) from a potential metal workshop area as indicated by surface finds, and C) from an area located in the settlement's centre. The samples were analysed by a portable X-ray fluorescence (pXRF) spectrometer in order to investigate the vertical and horizontal distribution of chemical signatures. The comparison of geophysical data and three-dimensional chemical patterns gives us the opportunity to determine the human impact and to reconstruct activity patterns. The potentials and limits in the application of pXRF in archaeological soil chemical surveys are evaluated by systematic comparisons with high resolution laboratory measurements, including atomic absorption spectrometry (AAS) and inductively coupled plasma optical emission spectrometry (ICP-OES). The pXRF analyses can be reproduced well and show a good accuracy. Whilst (p)XRF analyses reflect the total composition of archaeological soil samples, the results of the AAS and ICP-OES analyses are fundamentally influenced by the acid digestion or extraction methods used. The pXRF analyses of the Vráble soils showed typical patterns of human occupation. For example, there are strong positive correlations between phosphorous, strontium and calcium. Phosphorous shows an enrichment in pathways and the fortification ditch. It is less strongly enriched within the sediments of house structures. Similar results apply to calcium and strontium distribution. But compared to the respective concentrations in sediment samples from the ditch they show a considerably higher variation in samples associated with house structures; that is, individual samples of sediments from house structures contained high concentrations of both, calcium and strontium. The deposits of an area that according to surface finds was thought to represent a potential metal workshop did not show indicative chemical signatures. Targeted excavations confirmed the absence of such as workshop. Finally it was shown that the refill history of the innermost fortification ditch (sample area D) and the overall cultural occupation sequence at the site correlate strongly with the chemical signatures of the respective ditch profile. The systematic variation of key elements along the profile opens up an entirely new perspective for interpreting the site's history. Overall, the study shows the great potential of pXRF as valuable part of an archaeological survey toolkit.
Gesehen am 11.03.2021